Penerapan Model Pembelajaran Make A Match Untuk Meningkatkan Hasil Belajar Siswa - Mukhlisin, Mukhlisin (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2021)
The purpose of this study is to examine how the application and results of the make a macth learning method in improving student learning achievement. One of the tasks of the teacher as an educator is to carry out the learning process, not just learning, but effective learning, which is learning that is fun and gives positive results. One method that is able to give maximum results if applied correctly is the make a macth method. Learning methods that are included in the cooperative learning method are able to improve student achievement, both quantitatively and qualitatively. In terms of quantitative proven from the value of pretest, posttest I, and posttest II. Each of which reached 47.6%, 65% and 90% completeness. Whereas in terms of qualitative where students can: (1) increase curiosity and cooperation, (2) increase motivate students to help each other learn, (3). Foster a sense of responsibility, (4) improve social skills, (5) hone skills , and (6) can improve student leadership attitudes.